Design of An Appropriate Sunflower Threshing and Cleaning Machine for Small Scale Farmers. - Kabutetsi Charity (Kabale University, 2023)
Sunflower growing has become an important activity used to reduce food insecurity and improve on income of farmers. The objective of this study was to design an appropriate sunflower threshing and cleaning machine for small scale farmers. To achieve the objective of this study the following specific objectives had to be achieved: determining the design considerations of the sunflower thresher, sizing and selecting components and developing a layout of the machine.A survey of the existing threshing technologies and methods was carried out through observations.desk research from different sources and interviews in order to obtain data to help in specifying the design requirements, sizing and selecting components as well as generating a layout of machine. The different sources that were used include: text books, journals and websites.The study found out that sunflower threshing is mostly done manually though a few sophisticated machines have been employed in developed countries. The limitations of the existing sunflower threshing methods were found to be: expensive, large space requirement by the mechanized systems, labor-intensive, time consuming and tiresome for the case of manual threshing. Basing on the data collected through literature review, it was concluded that an appropriate sunflower thresher should be designed. The major components of the proposed machine were threshing chamber, threshing rotor, sieve, motor, blower, pulleys and frame. The layout of design was developed using solid works 2016 CAD software as per the dimensions of the individual components. The researcher, however, recommended that the fabrication of the machine needs to be done based on the individual part parameters developed and performance testing of the machine to embrace the new technology for effective threshing.